Atomic‐Precision Gold Clusters for NIR‐II Imaging. Issue 46 (1st October 2019) - Liu, Haile; Hong, Guosong; Luo, Zhentao; Chen, Junchi; Chang, Junlei; Gong, Ming; He, Hua; Yang, Jiang; Yuan, Xun; Li, Lulin; Mu, Xiaoyu; Wang, Junying; et al.
Abstract: Near‐infrared II (NIR‐II) imaging at 1100–1700 nm shows great promise for medical diagnosis related to blood vessels because it possesses deep penetration and high resolution in biological tissue. Unfortunately, currently available NIR‐II fluorophores exhibit slow excretion and low brightness, which prevents their potential medical applications. An atomic‐precision gold (Au) cluster with 25 gold atoms and 18 peptide ligands is presented. The Au25 clusters show emission at 1100–1350 nm and the fluorescence quantum yield is significantly increased by metal‐atom doping. Bright gold clusters can penetrate deep tissue and can be applied in in vivo brain vessel imaging and tumor metastasis. Time‐resolved brain blood‐flow imaging shows significant differences between healthy and injured mice with different brain diseases in vivo. High‐resolution imaging of cancer metastasis allows for the identification of the primary tumor, blood vessel, and lymphatic metastasis. In addition, gold clusters with NIR‐II fluorescence are used to monitor high‐resolution imaging of kidney at a depth of 0.61 cm, and the quantitative measurement shows 86% of the gold clusters are cleared from body without any acute or long‐term toxicity at a dose of 100 mg kg −1 . Abstract : Near‐infrared II (NIR II) imaging at 1100–1700 nm with deep penetration and high resolution shows great promise for medical diagnosis. Ultrasmall gold clusters with 1100–1350 nm NIR IIa emission are developed and can penetrate the skull of mouse. In vivo cerebrovascular and tumor metastasis imaging show that they serve as an NIR‐II fluorescence agent with potential clinical transformation for medical diagnosis.